1998
DOI: 10.1002/(sici)1097-4636(199807)41:1<65::aid-jbm8>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of glucose-sensitive hydrogels: Swelling and conductivity relationships

Abstract: The electrical characteristics of a glucose-sensitive polymeric hydrogel have been studied. The hydrogel matrices were prepared by radical polymerization of solutions containing 2-hydroxyethyl methacrylate, N,N-dimethyl aminoethyl methacrylate, tetraethylene glycol dimethacrylate, ethylene glycol, water, and glucose oxidase. The hydrogels displayed faster and higher swelling rates for lower levels of a crosslinking agent. Electrical conductivity was found to be a sensitive measurement of the state of the swell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…DMAEMA has been copolymerized with HEMA and crosslinked via a dimethacrylate molecule for the study of its biodegradability 16. Other copolymerizations of DMAEMA with HEMA have been described17, 18 to study the swelling behavior by electric measurements. However, no reports have focused on an analysis of the monomer reactivity ratios for this pair or for the copolymerization between EHMA and DMAEMA.…”
Section: Introductionmentioning
confidence: 99%
“…DMAEMA has been copolymerized with HEMA and crosslinked via a dimethacrylate molecule for the study of its biodegradability 16. Other copolymerizations of DMAEMA with HEMA have been described17, 18 to study the swelling behavior by electric measurements. However, no reports have focused on an analysis of the monomer reactivity ratios for this pair or for the copolymerization between EHMA and DMAEMA.…”
Section: Introductionmentioning
confidence: 99%
“…Although this field is very young, already a number of research groups worldwide has shown examples of stimulus‐responsive hydrogel sensors and actuators. These include, for example, hydrogel‐based pH 14–17, CO 2 13, 18 and glucose 19 sensors, a blood sampling system that uses a temperature‐responsive hydrogel to obtain a blood sample from a patient 20, hydrogel‐based fluidic components such as microvalves for the control of liquid flow through microchannels 9, 21–23, micropumps 24, as well as flow‐sorting 25 and mixing 26 systems. Eddington and Beebe presented a hydrogel‐based microdispensing device able to precisely deliver a given amount of fluid over a specified time 7.…”
Section: Introductionmentioning
confidence: 99%
“…It depends on the choice of carrier and the conditions of the immobilization process. Many references can be obtained in literature about immobilized GOD, where polymer and inorganic supports are the most common GoD carriers (2,6,12,14,19,23). Porous silica is certainly the most widely used because it is commercially available in a wide variety of shapes and sizes with different porosities.…”
Section: Introductionmentioning
confidence: 99%